2016
DOI: 10.1111/rmir.12064
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Barriers to Life Insurance Coverage: A Behavioral Approach

Abstract: While life insurance purchase decisions have long been studied, we still do not know how people decide if they need insurance or how much they need. Using in‐depth interviews, we peer into the black box of employee decision making to learn what people know about this employee benefit, and how they decide if it is of value for them. We find that individuals understand the need for life insurance, but find many behavioral economic barriers to getting adequate coverage, including mental accounting, money illusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 18 publications
1
12
0
1
Order By: Relevance
“…In the context of life insurance, studies in literature analysed the bounded rational behaviour of individuals and identified different behavioural biases that influence their decision to insure. Coe et al (2016) performed an experimental study on the employees of a company to understand their behaviour to purchase employee benefit plans by controlling the factors such as income, age, education, marital status and the number of children. The study found that employees were aware of life insurance's significance but were unable to decide an adequate amount of life insurance they should purchase.…”
Section: Behaviour-related Antecedentsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the context of life insurance, studies in literature analysed the bounded rational behaviour of individuals and identified different behavioural biases that influence their decision to insure. Coe et al (2016) performed an experimental study on the employees of a company to understand their behaviour to purchase employee benefit plans by controlling the factors such as income, age, education, marital status and the number of children. The study found that employees were aware of life insurance's significance but were unable to decide an adequate amount of life insurance they should purchase.…”
Section: Behaviour-related Antecedentsmentioning
confidence: 99%
“…The theory assumes that consumers purchase LIPs to maximize the beneficiary's utility (e.g., Alhassan & Biekpe, 2016;Ampaw et al, 2018); Andersson & Eriksson, 2015;Arun et al, 2012;Beck & Webb, 2003;Celik & Kayali, 2009;Chen et al, 2001). However, an inadequate amount of research is present in the literature on investigating consumers' bounded rational behaviour in a life insurance context based on the behavioural economics theory (Bauchet & Morduch, 2019;Coe et al, 2016). According to this theory, consumers often use some heuristics to estimate their probability of losses and estimate the gain and losses differently.…”
Section: Future Directions: Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…This may increase the tendency of individuals to follow heuristics and their proneness to behavioural biases which can influence default effects (Thaler and Sunstein, 2008). Therefore, there may be different decision processes that operate when defaults are applied within the LPHI risk context, compared to non-catastrophic risks which have been the focus of multiple studies on default effects (e.g., Johnson et al, 1993;Johnson et al, 2013;Coe et al, 2016;Krieger and Felder, 2013). This also highlights the innovation of a dedicated study of defaults under LPHI risk.…”
Section: Introductionmentioning
confidence: 99%